In vivo magnetization transfer imaging of the lung using a zero echo time sequence at 4.7 Tesla in mice: Initial experience. Issue 1 (13th August 2015) - Wurnig, Moritz C.; Weiger, Markus; Wu, Mingming; Kenkel, David; Jungraithmayr, Wolfgang; Pruessmann, Klaas P.; Boss, Andreas
Abstract : Purpose: The aim of the present study was to assess the feasibility of magnetization transfer‐prepared zero echo time (ZTE) imaging of the lung in vivo at high field strength [4.7 Tesla) T] in mice. Methods: Eighteen C57BL/10 mice underwent MRI examinations in a 4.7T MR‐scanner. A three‐dimensional ZTE sequence was applied for lung imaging combined with a Gaussian MT‐prepulse, which was followed by a train of 100 ZTE imaging readouts. Degree of MT was assessed by calculation of the magnetization transfer ratio (MTR). Direct saturation was estimated using Bloch equation simulations based on T1 measurements. The line‐width of pulmonary tissue was estimated using T2* measurements. Results: Experimental MTR‐values of nonpulmonary tissues obtained with ZTE exhibited the characteristics known from conventional MT‐sequences (skeletal muscle and liver: high values; fatty tissue: low values). Lung tissue demonstrated MTR‐values in between fatty tissue and liver tissue. Direct saturation could be estimated by the Bloch simulation; however, an adequate approximation was only possible for T2 values nearly in the range of parenchymal organs. Conclusion: Pulmonary MT measurements at high field strength using the proposed MT‐ZTE sequence is feasible; however, estimation of direct saturation remains challenging. Magn Reson Med 76:156–162, 2016. © 2015 Wiley Periodicals, Inc.